Distinct MLT asymmetry of auroral kilometric radiation observed by the FAST satellite - JiaWen Tang; Sai Zhang; FuLiang Xiao; HongMing Yang; Si Liu; YiHua He; Chang Yang; YuYue Jin; ZhouKun Deng; Ping Li; Archie James Johnston (Earth and Planetary Physics)
Auroral Kilometric Radiation (AKR) is a common radio emission, which can contribute to the magnetosphere−ionosphere−atmosphere coupling. Similar emissions have been observed in all magnetic planet magnetospheres of the solar system. In this study, using observations from the FAST satellite from 30 August 1996 to 9 September 2001, the distribution of AKR in altitude = 500−4500 km and invariant latitude (|ILAT|) = 60°−80° has been analyzed. 63045 AKR samples have been identified with ~48% (52%) samples on the dayside (nightside). Of considerable interest, there is a distinct MLT asymmetry with the high occurrence rate in MLT = 05−08 and 18−22 (02−05 and 12−17) in the northern (southern) hemisphere. The distinct MLT asymmetry is associated with the direction of \begin{document}$B_x$\end{document} of the interplanetary magnetic field. In addition, the occurrence rate on the nightside clearly increases as the \begin{document}$AE^*$\end{document} index increases. This study further enriches the information and understanding of AKR in the magnetosphere as well as other similar radio emissions.